The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/s-0039-3402084
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Diabetic Nephropathy in Streptozotocin-Induced Diabetic Rats by Acacia catechu Leaves Extract

Abstract: Objective The present study was performed to evaluate the ethanolic extract of leaves of Acacia catechu (A. catechu) for its effect on streptozotocin (STZ)-induced diabetes mellitus (DM) and its renal complications in male Wistar albino rats. Materials and Methods Male Wistar albino rats were grouped into control (A), STZ-induced DM (B), STZ-induced DM rats with A. catechu orally of 75 mg/kg body weight (kbw) for 35 days (C), with each group having six rats (n = 6) weighing between 200 to 250 g each.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The induction of diabetes caused an increase in serum levels of AST, ALT, urea and creatinine in animals as revealed by numerous works [3] [4] [11] [16]. In general, an increase in transaminases (AST and ALT) in the blood implies liver It therefore emerges from these observations that magnesium interacts positively with the secondary metabolites contained in Lippia multiflora aqueous leaves extract.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The induction of diabetes caused an increase in serum levels of AST, ALT, urea and creatinine in animals as revealed by numerous works [3] [4] [11] [16]. In general, an increase in transaminases (AST and ALT) in the blood implies liver It therefore emerges from these observations that magnesium interacts positively with the secondary metabolites contained in Lippia multiflora aqueous leaves extract.…”
Section: Discussionmentioning
confidence: 94%
“…In general, an increase in transaminases (AST and ALT) in the blood implies liver It therefore emerges from these observations that magnesium interacts positively with the secondary metabolites contained in Lippia multiflora aqueous leaves extract. These could include flavoids, alkaloids, tannins highlighted by various studies [2] [38] and whose hepatoprotective and nephroprotective actions have been demonstrated [16] [33] [39].…”
Section: Discussionmentioning
confidence: 99%
“…Acacia catechu leaves ameliorate Streptozotocininduced diabetic rats' nephropathy Moderate-tosevere degenerative characteristics, such as dilated tubules, degraded tubules, glomerular congestion, interstitial inflammatory infiltration, and atrophy of the glomerulus seen with dilated glomerular space, were visible in the extract and observation 82 .…”
Section: Acacia Catechu (Family -Fabaceae)mentioning
confidence: 94%
“…Abroma augusta (locally known as Ult kambal) leaf extract shows hypoglycemic effect on alloxan induced diabetic rats [ 29 ]. Acacia arabica (Fabeceae) bark exhibits antihyperglycemic effect in streptozotocin-induced diabetic rats [ 30 ].…”
Section: Introductionmentioning
confidence: 99%